Cinza de bagaço de cana-de-açúcar (CBC) como adição mineral em concretos para verificação de sua durabilidade - Fernandes, Sérgio Eduardo [UNESP]; Tashima, Mauro Mitsuuchi [UNESP]; de Moraes, João Cláudio Bassan [UNESP]; Istuque, Danilo Bordan [UNESP]; Fioriti, Cesar Fabiano [UNESP]; Melges, José Luiz Pinheiro [UNESP]; Akasaki, Jorge Luis [UNESP] (FapUNIFESP (SciELO), 2015)
The sugar-alcohol sector has been expanding in recent years, mainly by the advent of bioenergy. In Brazil, the production of sugarcane is increasing in areas before used for extensive cattle and other important crops, such as soybeans, corn and orange. In addition concerns about the generation of electricity by burning the bagasse (co-generation) and the use of ethanol as a fuel for motor vehicles. However, production of sugar, alcohol and energy from sugarcane can cause environmental problems due to the generation of waste, as the sugarcane bagasse ash (SCBA). In this way, this paper presents a viability study of using this ash from sugarcane bagasse obtained inthepower generation as mineral admixture in concrete. In this study, chemical characterization tests and x-ray diffraction of SCBA were carried out. Concrete were molded with SCBA replacing partially the fine aggregate, in mass, in the following percentages: 5%, 10%, 15% and 20%. Mechanical tests were carried out, and from the best results, were assessed indurability tests: resistance to chemical attack, wicking, chloride penetration and abrasion. The study was conductedthat SCBA presents low pozzolanic activity, however, the results indicated that the SCBAcould use as partial replacement of fine aggregate in the production of concrete, because its results are similar to reference concrete without the ash.
Sugarcane bagasse ash (GCB) as mineral admixture in concrete to check its durability
Keywords: Concrete; Durability; Sugarcane bagasse ash